Habitual Abortion in Hansen’s Morbus - Atfi, Ismi Mulya (Journal of Midwifery, 2023)
Based on WHO data, Indonesia is one of the countries contributing around 10,000 cases of Hansen’s morbus  2019. Hansen's morbus, or leprosy, is a chronic bacterial infection (Mycobacterium leprae) that attacks skin tissue, peripheral nerves, and the respiratory tract. Hansen's disease can occur during pregnancy and worsen during pregnancy. Pregnancy causes a relative decrease in cellular immunity. This can be explained because immunosuppression occurs during pregnancy. Pregnancy is dangerous for women with Hansen’s morbus . This case study describes a case of habitual abortion with Hansen’s morbus . The patient had a history of Hansen's morbus and had discontinued the medication. During pregnancy, the patient never underwent examination and treatment for Hansen's morbus. So, the patient experiences the habit of abortion. For this reason, it is necessary to carry out good treatment for pregnant women with Hansen's disease so that the mother and fetus receive appropriate treatment.